THE EFFECT OF PROFITABILITY ON TAX AVOIDANCE (CASE STUDIES OF MINING COMPANIES IN INDONESIA STOCK EXCHANGE (BEI) 2015-2019) - et. al., Fitri Sukmawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to find out the information presented about Good Corporate Governance, Profitability and tax avoidance in mining companies listed on the Indonesian Stock Exchange (IDX) for the 2015-2019 period.The method used in this research is verification and descriptive method with a quantitative approach.To measure the scale of research variables is the ratio scale, namely quantitative data in the form of numbers, the variables concerned are the independent Board of Commissioners, Managerial Ownership, and Institutional Ownership. The population that is the object of this study includes all financial reports of mining companies listed on the Indonesia Stock Exchange. The samples for the study were 5 financial reporting periods and 6 mining companies in accordance with the research criteria. The analysis used is panel data regression analysis, while the hypothesis is tested with the t test and F test. The mining companies are selected according to the criteria for the 2015-2019 period.Independent Board of Commissioners, Managerial Ownership and Institutional Ownership itability have a significant effect on Tax Avoidance